Flavobacterium acetivorans sp. nov. and Flavobacterium galactosidilyticum sp. nov., psychrotolerant flavobacteria isolated from cultivated fish - Saticioglu, Izzet Burcin; Ay, Hilal; Altun, Soner; Ajmi, Nihed; Gunduz, Enes Said; Gocmen, Huban; Duman, Muhammed (MICROBIOLOGY SOC, 2024)
Two yellow- coloured strains, F- 29T and F- 340T, were isolated from fish farms in Antalya and Mugla in 2015 and 2017 during surveillance studies. The 16S rRNA gene sequence analysis showed that both strains belong to the genus Flavobacterium. A polyphasic approach involving a comprehensive genome analysis was employed to ascertain the taxonomic provenance of the strains. The overall genome- relatedness indices of digital DNA-DNA hybridization (dDDH) and average nucleotide identity (ANI) between the strains and the other members of the genus Flavobacterium were found to be well below the established thresholds of 70 and 95 %, respectively. The whole- genome- based phylogenetic analysis revealed that strain F- 29T is closely related to Flavobacterium granuli (dDDH 39.3 % and ANI 89.4 %), while strain F- 340T has a close relationship with the type strain of Flavobacterium pygoscelis (dDDH 25.6 % and ANI 81.5 %). Both strains were psychrotolerant with an optimum growth temperature of 25 degrees C. The chemotaxonomic characteristics of the strains were typical of the genus Flavobacterium. Both strains had phosphatidylethanolamine, aminolipids and unidentified lipids in their polar lipid profile and MK- 6 as the isoprenoid quinone. The major fatty acids were iso- C15: 0 and anteiso- C15:0. The genome size of the strains was 3.5 Mb, while G+C contents were 35.3 mol% for strain F-29T and 33.4 mol% for strain F- 340T. Overall, the characterizations confirmed that both strains are representatives of two novel species within the genus Flavobacterium, for which the names Flavobacterium acetivorans sp. nov. and Flavobacterium galactosidilyticum sp. nov. are proposed, with F- 29T (JCM 34193T=KCTC 82253T) and F- 340T (JCM 34203T=KCTC 82263T) as the type strains, respectively.
Keywords: aquaculture; Flavobacterium; genome analysis; rainbow trout; IDENTIFICATION; DNA; Microbiology